Field-effect pump: liquid dielectrophoresis along a virtual microchannel with source-gate-drain electric fields. Issue 12 (22nd March 2021) - Wang, Fu-Min; Lu, I-Pei; Lin, Chih-Ting; Lu, Shey-Shi; Fan, Shih-Kang
Abstract : Field-effect pumps (FEPs) driving liquids continuously from source, via gate, toward drain electric fields along a virtual microchannel between parallel plates in linear, transition and saturation regions analogous to field-effect transistors (FETs). Abstract : We investigate liquid dielectrophoresis (LDEP) to implement field-effect pumps (FEPs) that drive liquids from source, via gate, toward drain electric fields between parallel plates without external pumps or the problem of dead volume. The appropriate gate electric field establishes a wall-less virtual microchannel to transfer the liquid from source to drain with an adjustable flow rate ( Q ) controlled by the difference of the square of the electric field strength (Δ E 2 DS ). Analogous to field-effect transistors (FETs), the FEPs can operate in a "linear", "transition" or "saturation" region depending on Δ E 2 GD and Δ E 2 DS . With a sufficient Δ E 2 GD and a small Δ E 2 DS, the FEPs operated in the linear region where Q was linearly proportional to Δ E 2 DS and inversely proportional to the flow resistance R that was mainly determined by the length ( L ), width ( W ) and height ( H ) of a stable and fully-occupied virtual microchannel. With an insufficient Δ E 2 GD and a moderate to large Δ E 2 DS, narrowing, tapering and even pinch-off of virtual microchannels were observed, which increased R and changed the operation into the transition or saturation region. A field-effect stream merger regulating two streams was built based on two FEPs with shared gate and drain electrodes. The versatility of FEPs was demonstrated with preliminary studies on whole blood and particle solutions.